2020
DOI: 10.3390/polym12010118
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate Modified GO Shape-Memory Polyurethane Composite

Abstract: Shape-memory composites have benefits for minimally invasive surgery, but their wider applications for bone repair are hindered by conflicts between the mechanical and memory performances, especially at load-bearing locations. In this study, we fabricated a graphene oxide shape-memory polyurethane composite through the chemical combination of graphene oxide and isocyanate, in order to realize satisfactory mechanical and shape-memory effects. As desired, a modulus of ~339 MPa and a shape recovery ratio of 98% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…21,22 On the basis of GO, it is possible for carboxyl, 23 amino, 24 hydroxyl 25 and other functional groups to be introduced not only to improve the fluidity and dispersion of graphene, but also to further endow it with new functions, among which is that various active substances can be loaded to improve bioactivities. 26,27 At present, the functionalized GDs have been compounded with various substrates such as metals, 28 inorganic, 29 natural polymer 30 and synthetic polymer 31 to prepare scaffolds, 32,33 coatings, 34 membranes 35 and injectable hydrogels. 36 Lots of studies in vitro and in vivo have demonstrated that the GDscontaining composites could regulate the extracellular microenvironment to effectively promote bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 On the basis of GO, it is possible for carboxyl, 23 amino, 24 hydroxyl 25 and other functional groups to be introduced not only to improve the fluidity and dispersion of graphene, but also to further endow it with new functions, among which is that various active substances can be loaded to improve bioactivities. 26,27 At present, the functionalized GDs have been compounded with various substrates such as metals, 28 inorganic, 29 natural polymer 30 and synthetic polymer 31 to prepare scaffolds, 32,33 coatings, 34 membranes 35 and injectable hydrogels. 36 Lots of studies in vitro and in vivo have demonstrated that the GDscontaining composites could regulate the extracellular microenvironment to effectively promote bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…339 MPa and the shape recovery ratio of 98% were obtained. After being implanted in a defective bone via a minimally invasive treatment, the composite ensured a generated force during the recovery process and seemed to provide a new possibility for a practical application of shape-memory polymers and composites in the field of bone repair [148]. nHAp/CNTs with GO and termed GNRs composites had good bioactivity and osseointegration properties for bone regeneration.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…On the other hand, GO nanostructures can be employed as nanofillers to strengthen mechanical properties of polymers [24] and can be used to fabricate artificial tough nacre of interest in aerospace applications [25,26]. Additionally, GO can endow with shape memory behavior to nanocomposites [27,28] for bone repair with minimal invasive surgery [29], and electrical actuators with low power consumption [30], essential for many applications in bioengineering. Recently, first-principle calculations have shown that GO with highly ordered epoxy groups can experience shape memory effect on its own without the presence of a polymer matrix [31,32] and can experience recoverable strain rates up to 14%.…”
Section: Introductionmentioning
confidence: 99%